Respostas

2014-04-28T19:02:47-03:00
3X-2X=3X-2  ( passa tudo pro 1º membro)
3x-3x-2x=-2
-2x=-2
x=-2/2
x= -1

2014-04-29T07:57:53-03:00
3x-2x=3x-2                                                                                                                  3x-2x-3x=-2                                                                                                                      1x-3x=-2                                                                                                                         -2x=2                                                                                                                             x=2/-2                                                                                                                         x=-1